Novel micellar CB2 receptor agonist with anti-inflammatory action for treating corneal alkali burns in a mouse model - Thathapudi, Neethi C.; Groleau, Marc; Degué, Delali S.; Aghajanzadeh Kiyaseh, Mozhgan; Kujawa, Piotr; Soulhi, Fouzia; Akla, Naoufal; Griffith, May; Robert, Marie-Claude (Frontiers in Pharmacology, 2023)
Introduction: Moderate corneal alkali burns such as those sustained from accidental exposure to household chemicals are treated with topical corticosteroids. Side effects include increased intraocular pressure and slowing of wound healing. Here, we compare the effects of a cannabinoid receptor 2 (CB2r) agonist, TA-A001, that is involved in wound healing with that of the corticosteroid, prednisolone. Methods: TA-A001 was encapsulated with a polymeric micelle comprising polyvinylpyrrolidone: polylactide block copolymers referred to as SmartCelle™ to allow delivery of the very hydrophobic drug. Mouse corneas were given moderate alkali burns. Different doses of TA-A001 of 0.125%, 0.25% and 0.5% were used to treat the burns in comparison to the corticosteroid, prednisolone. Results: TA-A001 at 0.25% and 0.5% allowed for faster wound closure. However, the higher 0.5% dose also induced unwanted neovascularization. By comparison, burned corneas treated with prednisolone showed slower healing as well as disorganization of the cornea. Although 0.25% TA-A001 appeared to produce the most-optimal responses, this dose resulted in marked expression of the macrophage chemoattractant protein, MCP-1. However, there was also an increase in CD163 positive stained M2 anti-inflammatory macrophages in the TA-A001 corneas. TA-A001 treated corneas showed the presence of sensory nerve fibers throughout the corneal epithelium including the superficial cell layers as did Substance P staining. Discussion: We found that TA-A001 at the 0.25% doses was able to modulate inflammation resulting from a moderate alkali burn to the cornea. With more extensive testing, TA-A001 might prove to be a potential alternative to corticosteroids for treating alkali burns or other causes of corneal inflammation.